FAKTOR YANG MEMPENGARUHI EMOSI REMAJA DI JORONG MURNI PANTI KENAGARIAN PANTI KECAMATANPANTI KABUPATEN PASAMAN - Yazid, Ahmad; Kasih, Fitria; Nofrita, Nofrita (Bimbingan dan Konseling, 2013)
This research departed from phenomena in the field, the adolescents feel very depressed by their parents so that there were from them who rebelled, and there are from them less of attantion of their parents, even there some parents giving more confidence to their children until made their children be sad , angry , daydreaming, fear ,shy, and often feel dissatisfied with what they have. Than this research raised about: Factors influencing adolescent emotions. The research purposes are to describe: 1) internal factors that influence adolescent emotions. 2) External factors that influence adolescent emotions. Techniques in this research is descriptive quantitative, this research population were all adolescents in Jorong Murni Panti. The sampling technique is the total sampling, a total sample of 47 people. The instrument used was a questionnaire, while the percentage of data analysis techniques used. Results of this research revealed that the internal factors that influence adolescent emotions are in many categories, and external factors that influence adolescent emotions were categorized lot. Based on the results of the research authors suggest to adolescents, in order to know the factors that influence emotions. To the Program, in order to give birth the teacher professional of GC. For writer self, in order to be material input and add insight about teenagers emotions.